2006
DOI: 10.1159/000098110
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of Thymidylate Synthase, Dihydropyrimidine Dehydrogenase and Thymidine Phosphorylase Expression in Colorectal Cancer Patients Receiving Adjuvant 5-Fluorouracil

Abstract: Objective: The combined assessment of thymidylate synthase (TS), dihydropyrimidine dehydrogenase (DPD) and thymidine phosphorylase (TP) gene expressions in metastatic colorectal cancer has been reported to be able to predict the efficacy of fluoropyrimidine-based chemotherapy. In order to evaluate the prognostic role in the adjuvant setting, we investigated the TS, DPD and TP expression in primary tumors of colorectal cancer patients treated with 5-fluorouracil (5-FU). Methods: TS, DPD and TP expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 63 publications
0
62
1
Order By: Relevance
“…As to the methodology of 5-FU metabolic pathway enzymes, protein activity, immunohistochemistry, enzymelinked immunosorbent assay (ELISA) and mRNA levels have been reported (13)(14)(15). Concerning the routine measurement of these enzymes, protein activity measurements are not technically feasible because of the complexity in the use of radioisotopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the methodology of 5-FU metabolic pathway enzymes, protein activity, immunohistochemistry, enzymelinked immunosorbent assay (ELISA) and mRNA levels have been reported (13)(14)(15). Concerning the routine measurement of these enzymes, protein activity measurements are not technically feasible because of the complexity in the use of radioisotopes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognostic value of these 5-FU-related metabolic enzymes in patients treated with 5-FU-based adjuvant chemotherapy is still controversial. It has been reported that a high-expression level of TS and low-expression levels of DPD were correlated with poor prognosis (13,14). In contrast, it has been reported that OPRT, though not TS and DPD have a prognostic value in patients treated with 5-FU-based adjuvant chemo-therapy (15).…”
Section: Introductionmentioning
confidence: 99%
“…Low levels or absence of DPD was associated with accumulation of 5-FU, leading frequently to significant toxicities and adverse events, even death. 55 There are studies supporting that increasing expression of DPD mRNA is associated with poor response to 5-FU and higher resistance, possibly because of a high catabolic rate. 42,56 Although low levels of DPD expose individuals to higher risk …”
Section: Cytotoxics: Pharmacogenetics and Molecular Markersmentioning
confidence: 99%
“…As a result, these enzymes have been studied extensively at the DNA, RNA, and protein levels, and high levels of expression by immunohistochemistry and mRNA associated with poor outcome. 1,[8][9][10][19][20][21][22] Recently, additional enzymes important in 5-FU effects have been identified, including mRNA expression of TNFRSF1B, SLC35F5, and orotate phosphoribosyltransferase. [23][24][25] At the DNA level, a tandem repeat of 28 bp is present in the 5 0 -untranslated region of the TS gene and is linked to its expression and enzymatic activity in tumors.…”
Section: Markers For Fluoropyrimidinesmentioning
confidence: 99%